Comparison of the prevalence of reversible airways obstruction in rural and urban Zimbabwean children. Issue 8 (August 1991) - Keeley, D J; Neill, P; Gallivan, S
Abstract : The prevalence of reversible airways obstruction has been assessed in children in three areas in Zimbabwe--northern Harare (high socioeconomic class urban children), southern Harare (low socio-economic class urban children), and Wedza Communal Land (rural children from peasant families). Peak expiratory flow (PEF) was measured before and after six minutes' free running in 2055 Zimbabwean primary school children aged 7-9 years. Height and weight were measured and nutritional state expressed as a percentage of the 50th centile for age (Tanner-Whitehouse standards). Reversible airways obstruction was deemed to be present when peak expiratory flow was below the 2.5th centile for height before exercise and rose by more than 15% after inhalation of salbutamol and when it fell by 15% or more after exercise and rose again after salbutamol. The prevalence of reversible airways obstruction was 5.8% (95% confidence interval 4.1-7.5%) in northern Harare (n = 726); 3.1% (1.8-4.5%) in southern Harare (n = 642), and 0.1% (0.0-0.4%) in Wedza (n = 687). In northern Harare, the only study area in which white children were found, the prevalence of reversible airways obstruction was similar in white (5.3%, 10/188) and black (5.9%, 32/538) children. Indicators of nutritional state also showed no significant differences between white and black children in northern Harare but were lower in southern Harare and lower still in Wedza. Urban living and higher material standards of living appear to be associated with a higher prevalence of reversible airways obstruction in children in Zimbabwe.